Fatal Pulmonary Embolism following Achilles Tendon Repair: A Case Report and a Review of the Literature - Asim M. Makhdom; Simon Garceau; Ronald Dimentberg (Case Reports in Orthopedics)
Deep venous thrombosis (DVT) is a significant source of morbidity in orthopaedic surgery. It can progress to a pulmonary embolism, a significant source of mortality. Up to date, patients with Achilles tendon rupture routinely do not receive DVT chemical prophylaxis. We are presenting a case of fatal pulmonary embolism after a surgically treated Achilles tendon rupture in a forty-two-year-old male healthy patient. In the current body of the literature, the reported incidence of DVT after Achilles tendon rupture is highly variable ranging from less than 1% to 34%, and there is a disagreement in the international guidelines regarding the need of chemical DVT prophylaxis with this type of injury. Further research needs to be conducted to investigate the risks and benefits of chemical DVT prophylaxis following Achilles tendon rupture. For low-risk patients, the use of milder forms of prophylaxis such as aspirin should also be explored.